2019
DOI: 10.1097/mpa.0000000000001311
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Analgesia Improves Postoperative Pain Control but Impedes Early Discharge in Patients Undergoing Pancreatic Surgery

Abstract: Objectives: Aim of this study was to evaluate the impact of epidural analgesia on postoperative length of stay, expeditious discharge, and pain relief after pancreaticoduodenectomy and distal pancreatectomy.Methods: Retrospective reviews of 2014-2015 American College of Surgeons National Surgical Quality Improvement Program databases and our institutional pancreas surgery database were conducted.Results: On univariate analysis, epidural analgesia was associated with statistically significant longer lengths of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Four studies [ 5 , 13 , 20 , 37 ] reported comparable pain scores on POD2 including a total of 565 patients (EDA: n =358, PCA: n =207) and found no significant difference in pain scores between EDA and PCA (SMD 0.29, 95% CI 0.83 to 0.24, p =0.19). Subgroup analysis of non-randomised studies also found no significant difference in pain scores (SMD 0.33, 95% CI 1.36 to 0.69, p =0.3) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies [ 5 , 13 , 20 , 37 ] reported comparable pain scores on POD2 including a total of 565 patients (EDA: n =358, PCA: n =207) and found no significant difference in pain scores between EDA and PCA (SMD 0.29, 95% CI 0.83 to 0.24, p =0.19). Subgroup analysis of non-randomised studies also found no significant difference in pain scores (SMD 0.33, 95% CI 1.36 to 0.69, p =0.3) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis of randomised studies was not possible. Three studies [ 5 , 13 , 20 ] reported pain scores on POD4 including a total of 463 patients (EDA: n =271, PCA: n =192). There was no significant difference in pain scores between EDA and PCA (SMD 0.08, 95% CI 0.26 to 0.06, p =0.18) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poorer analgesia compared to a well-controlled IV PCA may also reduce patient satisfaction [ 3 ]. Some studies have shown that thoracic epidural analgesia increased the complexity of recovery and rather increased the total hospital stay [ 20 ]. These studies explained that if epidural analgesia were performed in surgeries with short recovery periods, the start of anticoagulation after surgery was delayed, and the voiding rehabilitation period due to Foley catheter placement would be also required, which in turn delayed the recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreas transplant recipients often require increased anticoagulation due to the risk of allograft thrombosis, sometimes limiting the epidural options available [ 102 , 103 , 104 ]. Epidural analgesia is also known to increase the LOS while only providing superior pain control on the day of surgery in pancreatic surgery [ 105 ].…”
Section: Intra-operative Eras Componentsmentioning
confidence: 99%